ANALYSIS OF THE HEALT LEVEL OF THE NASARI SAVING AND LOAN COOPERATIVE IN AN EFFORT TO IMPROVE PERFORMANCE IN THE CITTY OF LHOKSMAWE - Yulius Dharma; Aulia, Nurul; Dwiyani, Uci; Hasan, Nadila; Sinta, Irada (RADJA PUBLIKA, 2023)
Savings and loan cooperatives generally provide services in order to facilitate the fulfillment of the needs of their members and ensure the welfare of their members. One of the goals of this cooperative is to serve as an alternative means of borrowing money or credit and trying to prevent its members from moneylenders. In the current development, savings and loan cooperatives are more in demand by credit seekers or customers, so that in line with that many Savings and Loans Cooperatives have been established which provide credit or loans to cooperative members without collateral, even though in banking principles every loan extension is always accompanied by a guarantee. This type of research uses qualitative methods. The population of the type of research conducted is research on a particular object by interviewing it at a certain time. The results of this study indicate that it is very easy to implement a credit agreement or save a loan at the Nasari Cooperative for retired civil servants. The agreement is made with the condition of a pension certificate scan. The Nasari Cooperative only makes special requirements for retirees who want to borrow to have a business. The purpose of this research is to provide an analysis of the soundness level of the Nasari Savings and Loans Cooperative in an effort to improve performance in the city of Lhoksmawe. Also, to know how the principle of operation is carried out by the cooperative. According to the results we examined and the conclusions we got are: KSP NASARI SYARIAH LHOKSEUMAWE is a financing institution for retirees, where they only provide credit financing for retirees who work at the post office and at banks which only work with the Nasari savings and loan cooperative. Credit financing by using a pensioner's scan and not serving general loans such as house certificates.